2020
DOI: 10.15728/bbr.2020.17.2.6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of crises on investments and financing of Brazilian companies: an approach in the context of financial constraints

Abstract: The purpose of this paper is to investigate the impacts of financial crises on investments and financing of constrained and unconstrained Brazilian firms, specifically analyzing the impact of the 2008 subprime crisis and the 2015 Brazilian economic crisis. For this purpose, the companies were classified as constrained or non-constrained by the criterion of the existence or non-existence of ratings, using quarterly data between Q1 2007 and Q3 2016, and adopting the panel analysis as the method. The results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…-USP, São Paulo institutions tend to be wary of granting credit, raising the cost of external financing (McLean & Zhao, 2014) and reducing investment as a whole. In Brazil, the recent crisis in 2015 negatively impacted company investments and this impact was greater over financially constrained companies (Franzotti & Valle, 2020). This type of environment worsens financial constraints through financial attrition, reducing the allocation of capital.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…-USP, São Paulo institutions tend to be wary of granting credit, raising the cost of external financing (McLean & Zhao, 2014) and reducing investment as a whole. In Brazil, the recent crisis in 2015 negatively impacted company investments and this impact was greater over financially constrained companies (Franzotti & Valle, 2020). This type of environment worsens financial constraints through financial attrition, reducing the allocation of capital.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Managers have more information than shareholders (Jensen & Mecking, 1976;Shaikh & O'Connor, 2020). Sometimes managers need to make decisions involving the sale of assets for various reasons (Campello, Graham & Harvey, 2010;Franzotti & Valle, 2020), but shareholders do not have information about the real reasons involved in the investment and divestment decisions regarding assets, due to the information asymmetry existing between the principal and the agent (Jensen & Mecking, 1976;Shaikh & O'Connor, 2020). On the one hand, companies invest for the most varied reasons: to increase production, technological innovation, productive efficiency, synergy in the business chain, industrial expansion (Fortunato et al, 2012), or profitability (Scherer;1965;Ross, 1995;Loss & Sarlo, 2006;Fortunato et al, 2012).…”
Section: Theoretical Referencementioning
confidence: 99%
“…Farmer (2017) argues that such uncertainties trigger distrust of financial markets, cause credit shortages and, consequently, restriction of funding sources (Damasceno, 2019). This event contributes to declining levels of investment (Barbosa, 2017;Farmer, 2017;Sarjono et al, 2021) and consumption (Barbosa, 2017) in ways that resonate with firm performance (Egbunike & Okerekeoti, 2018) and lead firms to cancel valuable investments (Campello, Graham & Harvey, 2010;Franzotti & Valle, 2020). Lima, Assaf, Perena and Silva (2011) reported that financial restrictions caused by economic crises contribute to a increase in the indebtedness of companies, which favors the occurrence of bankruptcies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations